Third European Conference on Web Services (ECOWS'05) 2005
DOI: 10.1109/ecows.2005.12
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Web services with diagnostic capabilities

Abstract: Fault management in Web Services composed by individual services from multiple suppliers currently relies on a local analysis, that does not span across individual services, thus limiting the effectiveness of recovery strategies. We propose to address this limitation of current standards for Web Service composition by employing Model-Based Diagnosis to enhance fault analysis. We propose to add Diagnostic Web Services to the set of Web Services providing the overall service, acting as supervisors of their execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 10 publications
(8 reference statements)
0
36
0
Order By: Relevance
“…The more comprehensive service logs are recorded, the more reliable diagnosis may be produced. Statistical studies have been reported in Wang et al (2005) and Ardissono et al (2005).…”
Section: The Diagnosis Phasementioning
confidence: 99%
“…The more comprehensive service logs are recorded, the more reliable diagnosis may be produced. Statistical studies have been reported in Wang et al (2005) and Ardissono et al (2005).…”
Section: The Diagnosis Phasementioning
confidence: 99%
“…Consistently with Model-Based Diagnosis, the analysis of the exceptions is carried out in a component-based way 1 by introducing local diagnostic services that analyze the internal behavior of the orchestrated Web Services, and by employing a global diagnostic engine to combine the local diagnoses. Each local diagnoser analyzes the behavior of the corresponding orchestrated Web Service WS i by utilizing a diagnostic model M i which describes the control and data flow of WS i by specifying the possible correct and incorrect behavior.…”
Section: Intelligent Exception Management Frameworkmentioning
confidence: 99%
“…H can be seen as the solution of a Constraint Satisfaction Problem [8] where constraints express the relation between failures and service behavior. See [1] for details about the adopted diagnostic algorithm.…”
Section: Smart Failure Identificationmentioning
confidence: 99%
See 2 more Smart Citations